Ética e corpo na formação docente em educação física - Brum, Lisiane Reis (My University, 2014)
Ethics, as philosophical reflection about the values that the human being takes and about the meaning of the actions that they practice, is essential in the training of Physical Education teachers, especially for developing a teaching practice directed toward the body and movement of human beings. The body, in Physical Education, can be understood by different ways, however, for the pedagogical practice of the teacher to be seen as an education directed to the totality of the human being, as a way of expression and physical communication, mental, emotional and social, we understand that teacher training in Physical Education requires constant attention on the issues focused on ethics and pedagogical implications about teaching practice with the body of others, considering the complexity that there is in different dimensions that characterize the human body. In view of the teachers training concerned to assist in reflection on ethics, body and education, we believe that the academic space is the way which it is possible to offer to the Physical Education´s graduate students the debate of these issues, since the teachers training is closely linked to the understanding of the whole process of learning and the teacher´s role in this process. This research aims to investigate how the degree course in Physical Education from a private institution has contributed to the formation of the ethical attitude of its students, considering the teaching practice with the body of others and considering that a specific look on attitudes in relation to others and about values assigned to the human body may have a direct relationship to the ethical education of each one. This study is related to the research line of History and Philosophy of Education and linked to the Project: Ethics in Teacher Training Program, of the Post-Graduation Program in Education at the University of Caxias do Sul. In order to provide elements that could answer the objective of this study, we analyzed the concepts of ethics and the body through the review of literature referenced by ideas of the philosophers Aristotle and Merleau-Ponty. The study is characterized as analyticaldescriptive, a qualitative approach. The instrument used for data collection was semistructured interview, the sample consisted of nine university teachers and thirteen students from bachelor´s degree in Physical Education, and we tried to verify the perception of respondents considering ethics, the body, the ethical attitudes of university teachers and its influence on the formation of an ethical conduct. For data analysis, we used the textual discourse analysis proposed by Moraes (2007). The study is divided into an introduction, a chapter referent to ethics and the body, another on the methodological framework and a final chapter with the analysis and interpretation of information, besides the final considerations about the research. We realized that students and professors are unanimous in the recognition of the importance of ethics for the harmonious relationship between human beings, whose term is seen by most as synonymous as moral and conducted to question of the action itself. The body is seen by teachers as physical, emotional and social totality, however, some students tend to see the body as a working tool, and they connect the body to the immediate logic of the labor market, without realizing the magnitude that there is around the human body. However, it is possible to say that the degree course in Physical Education contributes positively to the development of responsibility and commitment to teaching practice through the example of the attitudes of university teachers, whose teaching practice is characterized by respect and care for the human being totality, even if a minority of students are not yet prepared to realize this.
A ética, enquanto reflexão filosófica sobre os valores que o ser humano adota e sobre o sentido das ações que pratica, é essencial na formação de professores de Educação Física, especialmente por desenvolverem uma prática docente direcionada para o corpo e o movimento do ser humano. O corpo, na Educação Física, pode ser entendido à luz de múltiplos sentidos; no entanto, para que a prática pedagógica desse professor venha ao encontro de uma educação voltada para a totalidade do ser humano, como forma de expressão e comunicação física, psíquica, emocional e social, entende-se que a formação docente em Educação Física necessita constantemente de atenção, quanto aos aspectos voltados às implicações éticas e pedagógicas na prática docente com o corpo do outro, tendo em vista a complexidade existente nas diferentes dimensões que caracterizam o corpo humano. Na perspectiva da formação de professores preocupados em auxiliar na reflexão sobre ética, corpo e educação, acredita-se que o espaço acadêmico é o percurso pelo qual é possível oportunizar ao estudante de licenciatura em Educação Física o debate a essas questões, visto que a formação docente está estreitamente ligada ao entendimento de todo o processo de aprendizagem e da função do professor nesse processo. Esta pesquisa investigou como o curso Licenciatura em Educação Física de uma instituição particular tem contribuído para a formação da atitude ética de seus estudantes, na prática docente com o corpo do outro, tendo em vista que um olhar específico sobre as atitudes em relação ao outro, e sobre os valores atribuídos ao corpo humano, pode apresentar uma relação direta com a formação ética de cada um. Este estudo está situado na linha de pesquisa da História e Filosofia da Educação e vinculado ao Projeto Ética na Formação de Professores, do Programa de Pós-graduação em Educação da Universidade de Caxias do Sul. A fim de proporcionar elementos que permitissem responder ao objetivo do estudo, foram analisados os conceitos de ética e corpo mediante revisão da literatura referenciada pelas ideias dos filósofos Aristóteles e Merleau-Ponty. O estudo se caracteriza como analítico-descritivo, de cunho qualitativo. O instrumento utilizado para coleta das informações foi a entrevista semiestruturada, cuja amostra foi composta por nove professores universitários e treze estudantes do curso Licenciatura em Educação Física. Buscou-se verificar a percepção dos entrevistados em relação à ética, ao corpo, às atitudes éticas dos professores universitários e sua influência na formação de uma conduta ética. Para a análise dos dados, foi utilizada a análise textual discursiva proposta por Moraes (2007). O estudo está dividido em uma parte introdutória, um capítulo referente à ética e ao corpo; outro sobre a trajetória metodológica e um capítulo final com a análise e interpretação das informações, além das considerações finais sobre a pesquisa. Constatou-se que estudantes e professores universitários são unânimes quanto ao reconhecimento da importância da ética para o convívio harmonioso entre os seres humanos, cujo termo é percebido pela maioria como sinônimo de moral e conduzido à questão da ação propriamente dita. O corpo é percebido pelos professores como totalidade física, emocional e social; no entanto, alguns estudantes tendem a vincular o corpo a um instrumento de trabalho, visto que o conectam à lógica imediata do mercado de trabalho sem perceber a magnitude existente em torno do corpo humano. Contudo, é possível inferir que o curso Licenciatura em Educação Física contribui positivamente para o desenvolvimento da responsabilidade e do comprometimento com a prática de ensino, por meio das atitudes de exemplo dos professores universitários, cuja prática pedagógica se caracteriza pelo respeito e pelo cuidado com a totalidade do ser humano, mesmo que uma minoria de estudantes ainda não esteja preparada para perceber isso.
Keywords: Educação; Ética; Atitude ética; Corpo; Educação física - Educação; Professores - Formação; Ethics; Ethical attitude; Body; Physical education and training - Education; Training of teachers